Determinação das propriedades termomecânicas de ligas Cu-Al-Ni e Cu-Al-Be com efeito memória de forma para utilização como atuadores mecânicos - Oliveira, Danniel Ferreira de (2009)
Cu-Al-Ni and Cu-Al-Be shape memory alloys were cast under ambient atmosphere, and characterized thought optical microscopy, X-ray diffraction, and differential scanning calorimetry. Superelasticity, and shape recovery were evaluated using mechanical tensile test. Thermomechanical properties of shape memory alloys used were obtained under different temperature range, in which was possible to conclude that Cu-Al-Ni alloy can be used as mechanical actuators for temperatures above 90ºC, as well as this alloy in particular should not be considered for application in temperatures below 30ºC. Differently of CuAlBe alloy that can be used in low temperatures, as well as in temperature superiors to 0ºC, as, for example, mechanical actuators.